Influence of automated animal health monitoring and animal welfare label on consumer preferences and willingness-to-pay for filet mignon - Maselyne, Jarissa; Maes, Eva; Van De Gucht, Tim; Vandenbussche, Chari; Zwertvaegher, Ingrid; Van Weyenberg, Stephanie (Frontiers in Animal Science, 2024)
Precision Livestock Farming (PLF) has the potential to address some of the societal concerns regarding intensive livestock production, such as those with regard to animal health and welfare. However, information on the attitudes of consumers towards PLF is scarce. An online survey with a Discrete Choice Experiment was conducted in Flanders, Belgium to determine whether type of animal health monitoring (visual assessment without PLF, PLF at group level, PLF at individual level), animal welfare label (4 levels) and price influence the preference for filet mignon of consumers. In total, 454 respondents participated in the survey, of which 250 purchased filet mignon themselves. The characteristics gender, frequency of buying filet mignon, attitude towards organic and attitude towards welfare labels affected the utility (or "preferences") of the meat. The utility of was highest for female respondents, for respondents who bought filet mignon less than once a month, for those who consciously bought organic meat and those with a positive attitude towards labels guaranteeing animal welfare and health. The utility of filet mignon was not affected by the type of animal health monitoring, whereas animal welfare label and price had a significant effect. Respondents were willing to pay more for filet mignon carrying a welfare label, ranging from 15.2 €/kg (Label 1) up to 18.1 €/kg (Label 3) compared to a reference price of 12 €/kg (No label). Automated animal health monitoring did not have an influence on consumer preferences and willingness-to-pay for filet mignon. It should be further researched if consumers are neutral towards the use of PLF, or whether the technology might be relatively unknown.